Valorization of Coconut Shell and Blue Berries Seed Waste into Enhance Bacterial Enzyme Production: Co-fermentation and Co-cultivation Strategies - Khan P.A.; Singh T.; Lal B.; Singh R.; Syed A.; Verma M.; Mishra P.K.; Wong L.S.; Ahmad I.; Srivastava N. (My University, 2025)
Broad industrial application makes cellulolytic enzymes always in industrial demand with economic and sustainable production method. Production of cellulase enzymes via solid state fermentation mode using solid waste can resolve enzyme production and solid waste management issue in eco-friendly way. In present investigation, co-fermentation of solid wastes and microbial co-cultivation using potential cellulase producers strains have been applied as promising strategy for enhancement of cellulase at economical scale. Under the optimized bioprocess, co-fermentative substrate ratio of 5:4 of coconut waste (Ccw) and jamun fruits (JFs) gave 16 IU/gds filter paper (FP) activity at 12 h of incubation via bacillus strains in solid state fermentation (SSF). Additionally, at optimum production temperature of 42 °C and pH 6.0, enzyme showed 19 and 21 IU/gds FP activity at 12 h of incubation. Further, using different organic and inorganic sources, enzyme produced 26 IU/gds FP activity at 12 h peptone as nitrogen source. Additionally, at 60% optimum, moisture content, enzyme gave highest 31 IU/gds FP activity, 239 IU/gds, β-glucosidase (BGL) activity and 176 IU/gds endoglucanase (EG) activity in 12 h of incubation of SSF confirms the efficient production of all cellulolytic components of enzyme. The study has prominent scope in economical industrial application of this enzyme with promising waste management for environment sustainability applications. © Association of Microbiologists of India 2025.